Gut microbiota modulates seizure susceptibility. (29th July 2021) - Mengoni, Francesca; Salari, Valentina; Kosenkova, Inna; Tsenov, Grygoriy; Donadelli, Massimo; Malerba, Giovanni; Bertini, Giuseppe; Del Gallo, Federico; Fabene, Paolo Francesco
Abstract: A bulk of data suggest that the gut microbiota plays a role in a broad range of diseases, including those affecting the central nervous system. Recently, significant differences in the intestinal microbiota of patients with epilepsy, compared to healthy volunteers, have been reported in an observational study. However, an active role of the intestinal microbiota in the pathogenesis of epilepsy, through the so‐called "gut–brain axis, " has yet to be demonstrated. In this study, we evaluated the direct impact of microbiota transplanted from epileptic animals to healthy recipient animals, to clarify whether the microbiota from animals with epilepsy can affect the excitability of the recipients' brain by lowering seizure thresholds. Our results provide the first evidence that mice who received microbiota from epileptic animals are more prone to develop status epilepticus, compared to recipients of "healthy" microbiota, after a subclinical dose of pilocarpine, indicating a higher susceptibility to seizures. The lower thresholds for seizure activity found in this study support the hypothesis that the microbiota, through the gut–brain axis, is able to affect neuronal excitability in the brain.